Student mental health and engagement of students in a large online classroom setting during a global pandemic - Høyland-Kroghsbo, Nina Molin (Improving University Science Teaching and Learning, 2023)
This project was motivated by the challenge of engaging a large crowd of students over zoom during these “corona” times. Now, more than a year into the pandemic, I assumed that the students might be very tired of this format, potentially suffering from “zoom fatigue”. Therefore, I planned to engage the students via the online response system Mentimeter during zoom lectures and introduce “walk-and-talk” to allow students to build relationships in smaller groups while at the same time increasing their energy level and their creativity. Simultaneously, mounting accounts of declining student mental health due to social distancing and online teaching and an email from a concerned student spurred me to have an increased focus on student mental health.